Assessment of engineering gas radiative property models in high pressure turbulent jet diffusion flames. (September 2020) - Consalvi, J.L.; Andre, F.; Coelho, F.R.; Franca, F.H.R.; Nmira, F.; Galtier, M.; Solovjov, V.; Webb, B.W.
Highlights: Engineering global methods for gas radiation are considered. Comparisons are performed in several axisymmetric jet diffusion flames at high pressure. WSGG model is found to provide acceptable accuracy for engineering predictions. FSCK II and RC-SLW are found to be the most mature gas radiative property models to be implemented in CFD codes. Abstract: This article aims to determine the most relevant engineering global method for gas radiative property modeling to be applied in the simulations of combustion problems. Two versions of the full-spectrum correlated k (FSCK) model, the Rank-Correlated full-spectrum k -distribution/ Spectral-Line-Weighted-sum-of-gray-gases (RC-FSK/RC-SLW) and a new version of the Weighted-Sum-of-Grey-Gases (WSGG) model are compared with the Narrow-Band CK (NBCK) model in four turbulent axisymmetric jet diffusion flames fueled either by hydrogen or methane at atmospheric and higher pressures. These comparisons are performed in decoupled radiative heat transfer calculations with the thermal fields being prescribed. The databases and coefficients associated to these different models are determined from a unique Line-By-Line database in order to allow a relevant comparison. Model results suggest that the SLW/FSCK methods coupled to the so-called improved scheme proposed by Cai and Modest or the Rank-Correlated SLW/FSK model, along with k-g distributions generated from accurate high-resolution high-temperature databases are the most mature gas radiative property models to be implemented in CFD codes dealing with combustion problems involving gas-soot mixtures.